Determinants of Purchase Intention from A Perspective of Trust in Live Streaming E-Commerce: Literature Review - ZHANG YIFEI; ALBATTAT, AHMAD; NORHIDAYAH AZMAN; WEI MINGXIA (International Journal of Multidisciplinary Research and Studies, 2023)
Purpose: This study aims to explore the factors influencing purchase intention from the perspective of trust. Theoretical framework: Based on previous research, this study categorizes trust into trust in streamer, trust in product, and trust in platform as factors influencing consumers’ purchase intention. Design/methodology/approach: We gathered pertinent materials from academic publication databases, including Emerald, Science Direct, and Social Science Database. Referencing past literature to support the definition of variables in this study and the relationships between different forms of trust and purchase intention. Findings: Many past literature sources can confirm that trust in the streamer, trust in the product, and trust in the platform have a positive and significant impact on consumer's purchase intention in the context of live streaming. Research, Practical & Social implications: For research implications, the three types of trust proposed in this paper may offer future researchers research directions to explore newer models based on these concepts. In terms of practical implications, the findings of this paper can assist marketers in considering how to enhance trust in streamers, products, and platforms to increase consumer purchase intention. Originality/Value: The innovation of this study lies in exploring the impact of trust on consumer purchase intention from three perspectives: streamer, product, and platform. Particularly, building upon prior literature, this research introduces the perspective of live-streaming e-commerce platforms and presents a novel model.